Red Light Running Cameras: Would Crashes, Injuries and Automobile Insurance Rates Increase If They Are Used in Florida? - Barbara Langland-Orban; Etienne E. Pracht; John T. Large (University of North Florida, 2008)
Running a red light can cause severe traffic crashes especially when one vehicle runs into the side of another. Red light cameras photograph violators who are sent traffic tickets by mail. Intuitively, cameras appear to be a good idea. However, comprehensive studies conclude cameras actually increase crashes and injuries, providing a safety argument not to install them. Presently, Florida statutes do not permit red light camera evidence to be used as the sole basis for ticketing drivers for violating the law. Legislation to permit camera citations has been proposed since the 1990s, but none has passed to date. This paper explains red light running trends in Florida; effective solutions to reduce red light running; findings from major camera evaluations; examples of flawed evaluations; the automobile insurance financial interest in cameras; and the increased likelihood of even higher crash and injury rates if cameras are used in Florida due to the high percent of elderly drivers and passengers. The theory behind red light cameras as potentially effective is that they rely on deterring red light running primarily through punishment of a specific driving behavior and secondarily by changing drivers' experience. Because the rigorous and robust studies conclude that cameras are associated with increased crashes and costs, any economic analysis of cameras should include these newly generated costs to the public. Indirect costs to the public are usually not considered in the calculation of total revenues and profits generated from red light cameras. Florida should be cautious in using traffic safety information from the automobile insurance industry. Insurance financial goals are to increase their revenues and profits, which do not necessarily include reducing traffic crashes, injuries or fatalities. Also, public policy should avoid conflicts of interest that enhance revenues for government and private interests at the risk of public safety.